Revitalizing Nature’s Meaning in “Jabbaratul Ghabah” Short Story by Kamil Kailani: Shklovsky's Defamiliarization Study - Wananda, Anida Shofiyah; Halimi, Halimi (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
The impact of unusualness in literature is frequently employed by authors to create distinctive literary works. One technique that facilitates this uniqueness is defamiliarization. The objective of this study is to identify various defamiliarization techniques utilized by Kamil Kailani in his narrative and to elucidate the concept of natural revitalization as conveyed through the interactions between characters and nature in the short story "Jabbaratul Ghabah." This study adopts a descriptive qualitative approach, employing a text analysis framework informed by the theory of defamiliarization developed by Victor Shklovsky. Data collection methods include translation, reading, and note-taking, while the Miles and Huberman model is implemented for data analysis through classification, presentation, verification, and conclusion drawing. The findings indicate that "Jabbaratul Ghabah" features eighteen instances of defamiliarization across six techniques: personification, repetition, simile, metaphor, parallelism, and hyperbole. Among these techniques, two figurative meanings emerge: affirmation and comparison. Furthermore, the researcher identifies the meaning of natural revitalization inherent in the forms and techniques of defamiliarization. Kamil Kailani incorporates realities from the real world as the foundation for the narrative in "Jabbaratul Ghabah." Abstrak Efek ketidaklaziman dalam dunia kesusastraan seringkali digunakan oleh pengarang untuk melahirkan karya sastra yang unik. Defamiliarisasi merupakan salah satu teknik yang dapat digunakan untuk menciptakan keunikan tersebut. Tujuan dari penelitian ini adalah untuk mengungkap berbagai macam teknik defamiliarisasi yang digunakan Kamil Kailani dalam menarasikan ceritanya dan untuk mendeskripsikan makna revitalisasi alam yang disampaikan melalui adanya interaksi antara tokoh dan alam dalam cerita “Jabbaratul Ghabah”. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan pendekatan analisis teks yang didukung dengan teori defamiliarisasi yang dikembangkan oleh Victor Shklovsky. Adapun teknik pengumpulan data menggunakan teknik penerjemahan, baca, dan catat. Sedangkan model Miles dan Huberman digunakan untuk menganalisis data berupa klasifikasi data, penyajian data, verifikasi data, dan penarikan kesimpulan. Adapun hasil penelitian ini menunjukkan bahwa cerita pendek Jabbaratul Ghabah memiliki delapan belas bentuk defamiliarisasi dengan enam teknik yakni personifikasi, repetisi, simile, metafora, paralelisme, dan hiperbola. Dari enam teknik tersebut, terdapat dua makna kiasan berupa penegasan dan perbandingan. Selain itu, peneliti juga menemukan makna revitalisasi alam berdasarkan bentuk dan teknik defamiliarisasi. Terlebih, Kamil Kailani membawa realitas yang ada di dunia nyata sebagai dasar atas narasi dalam cerita pendek Jabbaratul Ghabah.